Evaluation of physical and chemical characteristics of sixty peanut germplasm - Erliana Ginting; NOVITA NUGRAHAENI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ginting E, Nugrahaeni N. 2020. Evaluation of physical and chemical characteristics of sixty peanut germplasm. Biodiversitas 21: 2840-2847. Nutritional values of peanut, particularly protein and fat is essential in terms of predominant use of peanut for foods. The seed size is also important for end use of the products. This study aimed to evaluate the physical and chemical characteristics of sixty ILETRI's peanut germplasm was performed. The results showed that the major genotypes had rose seed coat colors with two seeds per pod and average dried pod yield of 3.09 t/ha. Twenty-one genotypes belonged to large-seeded (? 55 g/100 seeds) and thirty-six were medium (40-55 g). The ash contents slightly varied from 2.53% to 2.98% (dw). One genotype (MLGA 0444) contained high protein (> 30% dw), while high-fat contents (> 43% dw) were noted in all genotypes. Selected genotypes had favored combinations of seed size, protein, and fat contents with high pod yield. Based on the similarity of 100-seed weights, ash, protein, and fat contents, sixty genotypes were grouped into three clusters with the main differences in seed sizes. Nineteen genotypes in cluster II with large seed size, medium protein, and high-fat content characteristics, particularly are suitable for oil extraction breeding purposes.